Advances in Nursery Production of Hazelnut Plants in Serbia − Successful Grafting of Different Corylus avellana L. Cultivars and Clones Onto Corylus colurna L. Rootstock - Bijelić, Sandra; Magazin, Nenad; Džankić, Sava; Janković, Draža; Bogdanović, Borivoje; Jaćimović, Goran (Frontiers in Plant Science, 2021)
The latest trends in hazelnut production are moving in the direction of selection and breeding of more productive cultivars, isolation of native clones and more intensive clonal selection of rootstocks aimed at enhancing the agronomic performance of plants. Serbia stands out in the production of quality planting material by grafting on Turkish filbert (Corylus colurna L.), which does not form shoots and develops in the form of a tree. The aim of this research was to investigate the success achieved by grafting leading Italian cultivars (Tonda Gentile Romana, Tonda di Giffoni and Tonda Gentile della Langhe) and their clones on Turkish filbert seedlings using technology developed at the University of Novi Sad, Faculty of Agriculture, Serbia, as well as determine possible differences in the quality and variability of the obtained planting material. For this purpose, from the end of March to the end of April, two-year-old Corylus colurna generative rootstocks (seedlings) were grafted by the whip and tongue method. At the beginning of September, the grafted plants were counted, and after the plants entered the dormant period (autumn in the year of grafting), they were taken out of the soil and classified. The obtained results revealed that the chosen hazel cultivars and clones exhibited excellent grafting success rate. In both analyzed years, as well as throughout the entire study period, greater grafting success was achieved using clones relative to the main cultivars. Over the two-year study period, the highest grafting success was achieved by clone AD17. Class I grafted plants were obtained in 80% of the cases, especially with Tombesi and AD17 clones, while significantly fewer Class I grafted plants were produced by grafting basic cultivars. Clones AD17 and Tombesi also produced grafted plants of greatest height and graft union diameter. All clones exhibited superior uniformity (i.e., a more stable grafting success) relative to their basic cultivars.